Cow’s milk exposure and atopic dermatitis after six months of age - Surya Jayanti Kadek; Dewi Kumara Wati Ketut; Karyana Putu Gede (Indonesian Pediatric Society, 2016)
Background About 60% of individuals with atopic dermatitis (AD) develop their first manifestation during infancy. Cow’s milk (CM) exposure is considered to be a risk factor for AD.Objective To evaluate for an association between cow’s milk exposure and atopic dermatitis in infants > 6 months of age. Methods This cross-sectional study consisted of subjects from a previous study and new subjects recruited in order to meet the minimum required number of subjects. Our study population comprised 120 infants, born between 1 February and 30 November, 2012 in Sanglah Hospital, Denpasar. Subjects were divided into CM and non-CM groups and analyzed for their risk of AD. Subjects were included to CM group if they were fed with cow’s milk/formula and included to non-CM group if they were breastfeed exclusively in the first six months of life. Other possible risk factors were assessed by multivariate analysis. Results One hundred twenty subjects were enrolled and analyzed (59 in the CM and 61 in the non-CM groups). The prevalence of AD was 30%. Multiple logistic regression analysis revealed a significant association between CM exposure and AD, with odds ratio (OR) 2.37 (95%CI 1.036 to 5.420; P=0.04). In addition, maternal diet including eggs and/or cow’s milk during the breastfeeding period was significantly associated with AD in infants (OR 3.18; 95%CI 1.073 to 9.427; P=0.04).Conclusion Cow’s milk exposure is significantly associated with atopic dermatitis in infants > six months of age.